Hat sizes and craniometry: Professional know-how and scientific knowledge. (April 2021) - Cryle, Peter
This article examines the relation between commercial activity and knowledge-making, looking at hatmakers in order to open up a more general question about the overlap between the knowledge practices of 19th-century science and those of everyday commercial culture of the time. Phrenology also claims attention here, since it can be said to have occupied an intermediate position between science and commerce. From time to time during the first half of the century, phrenologists attended to hatmakers in the hope of gleaning knowledge from their commercial experience, but after about 1860, scientific craniometers took a very different view. Physical anthropologists like Paul Broca believed that the skull was the key source of data on which to build a scientific anthropology of race or ethnicity. Observers drew the attention of Broca and his colleagues to the existence of a commercial device called the conformateur des chapeliers, used by hatters to determine head shape. But Broca was far less inclined to welcome hatmakers into the domain of craniology than the phrenologists had been. Whereas phrenologists had found validation in common sense, any widely available understanding of racial types was considered by Broca to be a distraction from the work of science and a potential distortion of its data. Far from the welcoming curiosity shown by London-based phrenologists, the anthropological enterprise led by Broca defined itself as scientific in part by the strictness with which it considered and dismissed such approximate and informal ways of knowing.